Nisā` Diction as the Concept of Women's Domestic Social Piety in al-Qur’an - Muhamad Hanif (IAIN Salatiga, 2021)
This library research analyzes the word Nisā` in al-Qur'an, which describes the women’s domestic roles and standards of social piety in Islamic view. It uses the philosophical-hermeneutical approach and social piety theory to analyze the data. This research results in three main findings: First, social piety in Islam manifests responsibility as God's caliphs on earth. Second, one of social piety description in Islam is by the use of word Nisā` repeatedly in different verses and surahs of al-Qur'an. The last, Nisā` diction to describe the social piety concept, according to al-Qur'an, places women in the domestic dimension to show women's participation as God's caliphs on earth in building the ideal social order. This research contributes to the gender studies overlooked by previous researchers, as the concept of Nisā` in al-Qur'an was ignored.